2000
DOI: 10.1002/jor.1100180607
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of chondrocytes from normal and osteoarthritic human cartilage

Abstract: The deformation behavior and mechanical properties of articular chondrocytes are believed to play an important role in their response to mechanical loading of the extracellular matrix. This study utilized the micropipette aspiration test to measure the viscoelastic properties of chondrocytes isolated from macroscopically normal or end-stage osteoarthritic cartilage. A three-parameter standard linear solid was used to model the viscoelastic behavior of the cells. Significant differences were found between the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
221
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 219 publications
(241 citation statements)
references
References 28 publications
17
221
3
Order By: Relevance
“…The increased stiffness (moduli) of osteoarthritic chondrocytes relative to non-osteoarthritic chondrocytes is generally consistent with those reported previously [48]. Although little difference in cytoskeletal distribution was seen in this study between non-osteoarthritic and osteoarthritic cells, previous studies with electron and confocal microscopy showed cytoskeletal alterations that were associated with cartilage degeneration.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The increased stiffness (moduli) of osteoarthritic chondrocytes relative to non-osteoarthritic chondrocytes is generally consistent with those reported previously [48]. Although little difference in cytoskeletal distribution was seen in this study between non-osteoarthritic and osteoarthritic cells, previous studies with electron and confocal microscopy showed cytoskeletal alterations that were associated with cartilage degeneration.…”
Section: Discussionsupporting
confidence: 92%
“…It is important to note that osteoarthritic cartilage is generally lacking a surface, or superficial zone, suggesting that the population of cells studied in this case includes a greater proportion of middle or deep zone cells as compared to non-osteoarthritic cartilage. In recent studies, we have shown little or no zonal variations in the mechanical properties of porcine chondrocytes from surface zone cartilage as compared to middle/deep zone tissue (Guilak, unpublished results), suggest that the observed differences between osteoarthritic and non-osteoarthritic chondrocytes are not simply due to alterations in the ratio of surface versus middle/deep cells studied [48].…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations